Working on the Margins in Metropolitan Los Angeles: Immigrants in Day-Labor Work - Valenzuela Jr., Abel (Migraciones Internacionales, 2017)
This article explores disadvantage theory for understanding the participation of Latino immigrants in day labor. Data from 481 randomly surveyed day workers at 87 hiring sites throughout Metropolitan Los Angeles make possible an examination of key demographic and labor market characteristics of this self-employed occupation. Even though the overwhelming majority of day laborers are recently arrived and unauthorized immigrants, not all are desperate, as disadvantage theory would have us believe. Day laborers are diverse in terms of their family structure, recency of arrival, tenure in day work, and human capital. Despite this diversity, lack of human capital and other characteristics generally handicap day laborers in their search for stable, better paying occupations in the non-day-labor market. Earnings among day laborers are mixed, hourly rates are higher than federal or state minimum-wage ceilings, bargaining is commonplace and advantageous to the worker, and wages are paid in cash and untaxed. However, these advantages are offset by unstable work patterns. For a minority of day laborers, this market provides an alternative to other forms of low-skilled, and irregular employment. Resumen Este articulo explora Ia teoría de Ia desventaja para entender Ia participación de inmigrantes Iatinos como jornaleros urbanos. Entrevistas con 481 jornaleros urbanos, seleccionados aleatoriamente en 87 lugares de empleo en el área metropolitana de Los Angeles, hacen posible un análisis de las características demográficas y del mercado de trabajo de este tipo de auto empleados. Aunque Ia gran mayoría de los jornaleros urbanos son inmigrantes recién llegados sin autorización para trabajar, no todos están desesperados, como Ia teoría de Ia desventaja podría hacernos creer. Los jornaleros urbanos son diversos en términos de su estructura familiar, el tiempo de su llegada, su experiencia en este trabajo y su capital humano. A pesar de esto, Ia falta de capital humano y otras características, generalmente los obstaculizan para buscar ocupaciones estables y mejor pagadas en el mercado laboral regular. Los ingresos entre los jornaleros urbanos son diversos, Ia paga por hora es mayor que los topes del salario mínima federal o estatal, el regateo de salarios es común y ventajoso para el trabajador y los salarios son pagados en efectivo y libres de impuestos. Sin embargo, estas ventajas son neutralizadas por Ia inestabilidad del trabajo. Para una minoría de jornaleros urbanos este mercado ofrece una alternativa a otros empleos irregulares y de baja calificación.